Girl Child - Hassman, Tupelo, 1973- (London Quercus, 2012)
Rory Dawn Hendrix is in a Girl Scout troop of one. She lives in a trailer park called the Calles de las Flores near Reno. And shes determined to leave, childless, before her sixteenth birthday. Easier said than done.
Keywords: Mothers and daughters -- Trailer camps -- Girls